2014
DOI: 10.1039/c4dt00051j
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of [K3(phen)8][Cu(NPh2)2]3—a possible intermediate in the copper(i)-catalyzed N-arylation of N-phenylaniline

Abstract: Complex [K3(phen)8][Cu(NPh2)2]3 (1, phen = phenanthroline) was isolated from the catalytic C-N cross coupling reaction based on the CuI-phen-tBuOK catalytic system. Complex 1 can react with 4-iodotoluene to give 4-methyl-N,N-diphenylaniline (3a) in 50% yield (based on all available NPh2(-) ligands of complex 1). In addition, 1 can also work as an effective catalyst for the C-N coupling reactions under the same reaction conditions, indicating that 1 may be an effective intermediate of the catalytic system. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Since a biphenyl structure sandwiched by two diarylamino groups has been attracting considerable attention as charge transport materials found in, for instance, organic light‐emitting diodes and photovoltaic cells, a heteroarylamine in hand was applied to construct such a related architecture but designed uniquely. Amongst a lot of candidates, we picked up 3 uf , which was then treated with 4,4′‐diiodobiphenyl ( 10 ) under the Ullmann−Goldberg conditions, thereby giving potentially useful structure 11 . It was found that 11 is a blue‐violet light‐emitting photoactive molecule with the emission maximum at 407 nm when excited at 265 nm in CH 2 Cl 2 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Since a biphenyl structure sandwiched by two diarylamino groups has been attracting considerable attention as charge transport materials found in, for instance, organic light‐emitting diodes and photovoltaic cells, a heteroarylamine in hand was applied to construct such a related architecture but designed uniquely. Amongst a lot of candidates, we picked up 3 uf , which was then treated with 4,4′‐diiodobiphenyl ( 10 ) under the Ullmann−Goldberg conditions, thereby giving potentially useful structure 11 . It was found that 11 is a blue‐violet light‐emitting photoactive molecule with the emission maximum at 407 nm when excited at 265 nm in CH 2 Cl 2 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…An umber of different ligand systems have been reported for accelerating the modified Ullmann reaction, with perhaps one of the most studied being 1,10-phenanthroline (phen). Phen has been shown to significantly improvet he yields and reaction rates in the arylation of arylamines, [4][5][6][7][8][9] hydrazines [71] and aliphatic alcohols. [72,73] However,s tudies employing this ligand in alkylamine-aryl coupling reactions are less well documented, with diketone and amino acid based ligandsm ore often employed.…”
Section: Identification Of Solution Structures Of Complexes 3a Nd 4i mentioning
confidence: 99%
“…The effect of phen on the reactivity of 3 was more pronounced when [D 6 ]DMSO was used as the solvent, with the yield unexpectedly decreasing from 75 %t o2 6%.T he yields obtained with complexes 4 and 5 on addition of phen were also diminished in [D 6 ]DMSO compared to their ligand-free analogues.T hese resultsa re somewhat surprising in light of the prominentr ole played by phen in copper-catalysed Ullmann amination. [4][5][6][7][8][9] Nevertheless, they can be explained in the context of the solution studies which showedt he favoured formation of the ionic cuprate species (III,S cheme 4) on addition of phen to copper(I) amide in DMSO.P revious studies on the reactivity of isolatedb isamidocuprate complexes [Cu(NR 2 ) 2 ] À (NR 2 = NPh 2 ; [30] phthalimidate [29] )h ave shown these anionic speciestohave little or no reactivity in the cross-coupling reaction with aryl halides. If, as seems likely,t he bis(dialkylamino)cupratec omplexes present in the reactionm ixture here also exhibit low reactivity,t his could help explain the observed reductioni np roduct yield.…”
Section: Identification Of Solution Structures Of Complexes 3a Nd 4i mentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of the second dendron: N,N ‐di(4‐tolyl)‐4’‐iodophenylamine (12) was also achieved in a straightforward manner. A ready available di‐tolylamine 9 was coupled with iodobenzene 10 using a modified Ullmann protocol . The substituted triphenylamine derivative 11 obtained in this way was subjected to an aromatic iodination procedure to afford 12 in good yield (Scheme ) …”
Section: Resultsmentioning
confidence: 99%